A Danish Profiling System - Michael Rosholm; Michael Svarer; Bo Hammer (Institute for the Study of Labor (IZA), 2004)
We describe the statistical model used for profiling new unemployed workers in Denmark. When a worker – during his or her first six months in unemployment – enters the employment office for the first time, this model predicts whether he or she will be unemployed for more than six months from that date or not. The case workers? assessment of how to treat the person is partially based upon this prediction.
Keywords: J64; J68; 330; unemployment duration; profiling; Arbeitslosigkeit; Personalbeurteilung; Arbeitsmarktpolitik; Dänemark